The rhetorical purpose of the battle between protagonist and antagonist in 2 Maccabees 9 - Cornelius, Elma (Stellenbosch Theological Journal, 2020)
The main theme in 2 Maccabees seems to be the use and abuse of "power". The very striking battle for power, as presented in 2 Maccabees 9, is the focus of this article. The research questions are: Who are the protagonist and the antagonist in 2 Maccabees 9? How does this chapter describe these characters? What is the nature of the struggle between the protagonist and antagonist? What is/are the rhetorical function(s) of the struggle in 2 Maccabees 9? What is the rhetorical purpose of 2 Maccabees 9? As 2 Maccabees is a narrative, written in a world where rhetoric played an important role in communication, the text is interpreted with the help of rhetorical criticism and narrative criticism. Attention will be given to specifically the text's description of the antagonist and protagonist and the rhetorical function(s) of these descriptions will be interpreted. As the use and abuse of power play such an important role in the description of these characters, the phenomenon of power will be interpreted by using definitions and discussions by sociologists and psychologists where relevant. It is concluded that the text of 2 Maccabees 9 aims at moving the reader from an attitude of doubt and distrust in God, because of the bad things that happened, to an attitude of trust and obedience in God, who is just and powerful. God is presented as the supernatural power, with the implicit warning that no human being can ever affect this power. It is a message of hope for the victims of power abuse. It is a piece of advice and a warning to be spiritually intelligent and to hold on to the almighty power of God, with the promise that God will always be there, listen to the prayers of believers and act in love towards them. It is also a warning to never oppose God. The reader is persuaded in 2 Maccabees, especially in Chapter 9, of the advantages of a spiritual intelligence. It clearly demonstrates that no abuse of power by humankind, can ever limit the power of God.